2015
DOI: 10.1080/15592294.2015.1048060
|View full text |Cite
|
Sign up to set email alerts
|

Identification of differentially methylated markers among cytogenetic risk groups of acute myeloid leukemia

Abstract: Abbreviations: AML, acute myeloid leukemia; CHARM, comprehensive high-throughput array-based relative methylation analysis; DMR, differentially methylated region; TCGA, The Cancer Genome Atlas Research NetworkAberrant DNA methylation is known to occur in cancer, including hematological malignancies such as acute myeloid leukemia (AML). However, less is known about whether specific methylation profiles characterize specific subcategories of AML. We examined this issue by using comprehensive high-throughput arra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
(34 reference statements)
0
20
0
Order By: Relevance
“…Genetic subtypes of childhood ALL and AML have been associated with DNA methylation signatures . A recent study by Amabile et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic subtypes of childhood ALL and AML have been associated with DNA methylation signatures . A recent study by Amabile et al.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic subtypes of childhood ALL and AML have been associated with DNA methylation signatures. [24][25][26] A recent study by Amabile et al showed that in a murine chronic myeloid leukemia (CML) model, induction of BCR-ABL could trigger DNA methylation changes. Furthermore, it was shown that aberrant DNA methylation had the potential to contribute to leukemia progression in primary CML cells.…”
Section: Discussionmentioning
confidence: 99%
“…Other groups demonstrated that HoxA13 was associated with the development of monocytes and macrophages, and its expression was observed more often in monocytic leukemia cell lines in comparison with other types of leukemia [40]. Moreover, the expression of genes HOXB3 and HOXB4 has been found to be altered in patients with AML with poor prognosis [41].…”
Section: Hematopoiesismentioning
confidence: 98%
“…Considering the fact that UHRF1 is overexpressed in various solid [5, 24] and haematological tumors [25, 26] and that UHRF1 via its domains (Fig. 1) guarantees a strong relationship between DNA methylation and histone post-translational changes [5, 6, 27, 28], targeting this epigenetic actor could be a new promising anticancer strategy.…”
Section: Introductionmentioning
confidence: 99%